Nutraceutical Properties and Toxicity Studies of Flour Obtained from Capsicum pubescens Fruits and Its Comparison with “Locoto” Commercial Powder - Rivas, Marisa Ayelen (2014)
The aim of this research was to evaluate the phytochemical profiles of flour from red, yellow and green fruits of Capsicum pubescens (commun name: locoto) and compare with “locoto” commercial powder (Lcp). Soluble protein (SP), total sugar (TS), free phenolic compounds (FPC), ascorbic acid (AA), total monomeric anthocyanin (TMA), condensed and hydrolizable tannin (CT, HT) and carotenoids (C) were determined by spectrophotometric methods. Multielemental composition by ICP-MS was also done. The flour showed low amounts of calories and high potassium and low sodium levels. Flour from “locoto” fruits contained mainly carotenoids (0.82 to 20 g Eβ-C/100g DW), polyphenolic compounds (681 - 822 mg GAE/100g DW) and ascorbic acid (100 - 199 mg AA/100g DW). The polyphenolic profile of Lcp was similar to flour obtained in our laboratory but the level of carotenoid was lower than that of flour. The fiber content of flour was around 3% in all cases. All preparations obtained from flour and Lcp showed antioxidant activity with SC50 values between 1.4 and 3 μg GAE/mL. Inhibitory capacity on Lipo-oxygenase enzyme was also demonstrated. Non mutagenic effect was detected. The “locoto” flour showed nutraceutical characteristics that are demanded by functional food and could be used as a dietary supplement.